(untitled) (Amsterdam, 2008)
Information Assurance skillfully addresses this issue by detailing the sufficient capacity networked systems need to operate while under attack, and itemizing failsafe design features such as alarms, restoration protocols, and management configurations to detect problems and automatically diagnose and respond. Moreover, this volume is unique in providing comprehensive coverage of both state-of-the-art survivability and security techniques, and the manner in which these two components interact to build robust Information Assurance (IA). Thebook to combine coverage of both security AND survivability in a networked information technology setting:Leading industry and academic researchers provide state-of-the-art survivability and security techniques and explain how these components interact in providing information assurance, Additional focus on security and survivability issues in wireless networks.
Keywords: Computer networks,Mạng máy tính; Security measures.,Tiêu chuẩn an toàn